Low-level cadmium exposure induced hormesis in peppermint young plant by constantly activating antioxidant activity based on physiological and transcriptomic analyses - Wang, Bin; Lin, lvna; Yuan, Xiao; Zhu, Yunna; Wang, Yukun; Li, Donglin; He, Jinming; Xiao, Yanhui (Frontiers in Plant Science, 2023)
As one of the most toxic environmental pollutants, cadmium (Cd) has lastingly been considered to have negative influences on plant growth and productivity. Recently, increasing studies have shown that low level of Cd exposure could induce hormetic effect which benefits to plants. However, the underlying mechanisms of Cd-triggered hormesis are poorly understood. In this study, we found that Cd stress treatment showed a hormetic effect on peppermint and Cd treatment with 1.6 mg L-1 concertation manifested best stimulative effects. To explore the hormesis mechanisms of Cd treatment, comparative transcriptome analysis of peppermint under low (1.6 mg L-1) and high (6.5 mg L-1) level of Cd exposure at 0 h, 24 h and 72 h were conducted. Twelve of differentially expressed genes (DEGs) were selected for RT-qPCR validation, and the expression results confirmed the credibility of transcriptome data. KEGG analysis of DEGs showed that the phenylpropanoid biosynthesis and photosynthesis were important under both low and high level of Cd treatments. Interestingly, GO and KEGG analysis of 99 DEGs specifically induced by low level of Cd treatment at 72 h indicated that these DEGs were mainly involved in the pathway of phenylpropanoid biosynthesis and their functions were associated with antioxidant activity. The expression pattern of those genes in the phenylpropanoid biosynthesis pathway and encoding antioxidant enzymes during 72 h of Cd exposure showed that low level of Cd treatment induced a continuation in the upward trend but high level of Cd treatment caused an inverted V-shape. The changes of physiological parameters during Cd exposure were highly consistent with gene expression pattern. These results strongly demonstrate that low level of Cd exposure constantly enhanced antioxidant activity of peppermint young plants to avoid oxidative damages caused by Cd ion, while high level of Cd stress just induced a temporary increase in antioxidant activity which was insufficient to cope with lasting Cd toxicity. Overall, the results presented in this study shed a light on the underlying mechanisms of the Cd-mediated hormesis in plant. Moreover, our study provided a safe method for the efficient utilization of low Cd-contaminated soil as peppermint is an important cash plant.